WR 2020
DOI: 10.37763/wr.1336-4561/65.1.161174
|View full text |Cite
|
Sign up to set email alerts
|

Tang Dynasty Chair Feature Design Based on Kansei Evaluation and Eye Tracking System

Abstract: Tang dynasty (AD 618-907) chairs were manufactured during an important period of Chinese furniture development. This paper aims to identify design elements that impact on people's subjective impressions, so as to guide the design of Tang dynasty style chairs. The study combined eye tracking and Kansei evaluation methods to assess the semantic reception of Tang dynasty chairs. The results showed that the influential factors can be grouped into two main categories: decoration and shape. The decorative features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The possible reason is that the difference between our experimental stimuli is not enough to cause significant changes in EDA, while the HRV, which is also commonly used in emotional measurement, has an evident discrepancy in our study, which may indicate that the threshold of stimuli that can cause obvious changes in EDA is higher than that of the HRV. The adoption of eye-tracking was due to its role in the study of visual preference, which can reflect visual cognitive and psychological processes [36,37]. Kaihong Zhang et al showed that the change in pupil diameter was negatively correlated with visual comfort in the study of stereo image chromaticity [21].…”
Section: Correlated Color Temperature and Psychophysiological Variablesmentioning
confidence: 99%
“…The possible reason is that the difference between our experimental stimuli is not enough to cause significant changes in EDA, while the HRV, which is also commonly used in emotional measurement, has an evident discrepancy in our study, which may indicate that the threshold of stimuli that can cause obvious changes in EDA is higher than that of the HRV. The adoption of eye-tracking was due to its role in the study of visual preference, which can reflect visual cognitive and psychological processes [36,37]. Kaihong Zhang et al showed that the change in pupil diameter was negatively correlated with visual comfort in the study of stereo image chromaticity [21].…”
Section: Correlated Color Temperature and Psychophysiological Variablesmentioning
confidence: 99%
“…Eye movement data reflect objective indicators of human eye movement behavior and focus of attention, and each indicator has a specific meaning and scope of application (Chang et al 2016). It is one of the focuses of this study to select appropriate indicators to establish the relationship between eye movement data and user morphological elements intention preference (Zhagn and Xu 2020). Through eye-tracking technology, one can extract the elements of furniture shape design, study the cognitive intention preference of shape features, and study the color preference of furniture (Xu and Zhang 2012;Liu et al 2018).…”
Section: Eye Tracker and Furniture Designmentioning
confidence: 99%
“…Liu designed two new Chinese style chairs, which provided ideas and opportunities for the inheritance and development of the furniture culture of the Ming and Qing Dynasties, and broadened the vision of modern chair design. Zhang and Xu (2020) reconstructed the shape of the chair according to the shape of the chair in Tang Dynasty (China) paintings, the proportions of the chairs compared to people in the paintings, the information regarding the size of the surviving Tang dynasty chairs, and the information recorded in ancient paintings. According to the molding of these chairs, the proportion and form of chairs in the Tang Dynasty were estimated.…”
Section: Introductionmentioning
confidence: 99%